2020
DOI: 10.1083/jcb.201912081
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal organization of axons in vertebrates and invertebrates

Abstract: The maintenance of axons for the lifetime of an organism requires an axonal cytoskeleton that is robust but also flexible to adapt to mechanical challenges and to support plastic changes of axon morphology. Furthermore, cytoskeletal organization has to adapt to axons of dramatically different dimensions, and to their compartment-specific requirements in the axon initial segment, in the axon shaft, at synapses or in growth cones. To understand how the cytoskeleton caters to these different demands, this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 276 publications
(382 reference statements)
4
75
0
Order By: Relevance
“…As another example, we found that loss of either Eb1, XMAP215/Msps or Tau all caused a reduction in comet numbers, potentially reflecting changes in MT nucleation activity, consistent with reports of nucleation-promoting roles of XMAP215 (Flor-Parra, Iglesias-Romero et al, 2018, Roostalu, Cade et al, 2015, Thawani, Kadzik et al, 2018, Wieczorek, Bechstedt et al, 2015. Extending work from MT polymerisation to nucleation is possible in the fly system and would have the potential to deliver explanations for how numbers of MTs can be regulated in reproducible, neuron-specific ways, thus addressing a fundamental aspect of axon morphology (Prokop, 2020).…”
Section: Main Conclusion and Future Perspectivessupporting
confidence: 81%
See 2 more Smart Citations
“…As another example, we found that loss of either Eb1, XMAP215/Msps or Tau all caused a reduction in comet numbers, potentially reflecting changes in MT nucleation activity, consistent with reports of nucleation-promoting roles of XMAP215 (Flor-Parra, Iglesias-Romero et al, 2018, Roostalu, Cade et al, 2015, Thawani, Kadzik et al, 2018, Wieczorek, Bechstedt et al, 2015. Extending work from MT polymerisation to nucleation is possible in the fly system and would have the potential to deliver explanations for how numbers of MTs can be regulated in reproducible, neuron-specific ways, thus addressing a fundamental aspect of axon morphology (Prokop, 2020).…”
Section: Main Conclusion and Future Perspectivessupporting
confidence: 81%
“…We propose that similar mechanisms might operate in smaller diameter axons in vertebrates, such as in parallel fibres of the cerebellum where Tau has demonstrated structural roles (Harada, Oguchi et al, 1994); they might explain the aforementioned findings of small Eb protein comets in cultured vertebrate neurons, as well as the reduction in MT numbers observed upon loss of Tau in C. elegans (Krieg, Stühmer et al, 2017). However, in larger diameter axons of vertebrates where MT densities are low (Prokop, 2020), the Eb1 depletion effect might be far less noticeable.…”
Section: Eb1 and Xmap215/msps Are Core Factors Promoting Mt Polymerismentioning
confidence: 77%
See 1 more Smart Citation
“…Neurofilaments are neuron-specific intermediate filaments that are stretch-resistant and are major cytoskeleton proteins [ 114 ]. They form parallel coiled-coiled heterotetramers composed of light, medium, and heavy-weighted neurofilaments (NF-L, NF-M, and NF-H, respectively) and α-internexin or peripherin [ 112 , 114 ]. Eight heterotetramers form cylindrical structures known as unit-length filaments (ULFs) with the tail domains sticking out [ 112 , 114 ].…”
Section: Axonal Transportmentioning
confidence: 99%
“…They form parallel coiled-coiled heterotetramers composed of light, medium, and heavy-weighted neurofilaments (NF-L, NF-M, and NF-H, respectively) and α-internexin or peripherin [ 112 , 114 ]. Eight heterotetramers form cylindrical structures known as unit-length filaments (ULFs) with the tail domains sticking out [ 112 , 114 ]. A series of ULFs form a filament that matures into neurofilament after a radial compaction of the cylindrical structure [ 112 ].…”
Section: Axonal Transportmentioning
confidence: 99%